Sol–gel synthesis of SiO2–CaO–P2O5 glasses: Influence of the heat treatment on their bioactivity and biocompatibility. Issue 10 (December 2015) - Catauro, M.; Bollino, F.; Renella, R.A.; Papale, F.
Abstract: The main goal of the present work is to synthesize SiO2 ·CaO·P2 O5 bioactive glasses by a sol–gel method. The influence of the Ca/P molar ratio and of heat treatment on the biological properties of the glassy materials has been investigated. Two gels with different Ca/P molar ratios have been prepared. The gels obtained have been subjected to heat-treatment at three different temperatures: 120 °C, 600 °C and 1000 °C. The bioactivity of the glasses has been evaluated by soaking the samples in a simulated body fluid. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM) allowed the presence of an hydroxyapatite layer on the surface of the samples after 7, 14 and 21 days of exposure to be detected. Moreover, the biocompatibility of the obtained glasses has been assessed by means of WST-8 assay using NIH 3T3 murine fibroblast cells. It has been shown that both the Ca/P molar ratio and heat-treatment have a significant influence on the biological properties of the materials. The sample with the higher calcium content and heat-treated at 600 °C has been found to be the most bioactive. The biocompatibility of the materials treated at 600 °C and 1000 °C is much higher than that of those heated at 120 °C.